Site-directed mutagenesis of the acidic interdomain linker FVIIIa3 of the coagulation factor VIII as a strategy to favor crystallization of its complexes with thrombin - Rojas-Murcia, Jeremy (2019)
Cardiovascular diseases are one of the most important causes of morbidity and mortality worldwide, which translates into a strong economic impact in the health sector. Factor VIII (FVIII) is an essential cofactor within the hemostatic processes involved in blood clot formation upon vascular damage. The proteinase thrombin is the most important physiological activator of FVIII, but the molecular mechanisms underlying recognition of FVIII by thrombin and the formation of the corresponding, transient Michaelis-Menten complexes are still only poorly understood. X-ray crystallography allows the resolution of the 3D structure of protein complexes, but a prerequisite is the crystallization of the sample to be analyzed. To grow crystals of the human FVIIIa3 (residues Glu1649-Arg1689) complexed with thrombin, site-directed mutagenesis was performed to generate the double-mutants FVIIIa3 (R1689Q, G1690P) and FVIIIa3 (R1689G, G1690P). Both fragments were overexpressed as heterologous proteins and purified with yields of ~1.5 mg per liter of bacterial culture. Availability of these recombinant proteins allowed in turn generation of FVIIIa3 (R1689Q, G1690P)•thrombin and FVIIIa3 (R1689G, G1690P)•thrombin complexes to perform extensive screenings of their solubility space. Altogether, a total of 630 to 820 different crystallization conditions were evaluated for both complexes. From these initial screen, some sort of crystalline precipitate was obtained in 22 conditions, 10 of which could be optimized to grow high-quality single crystals for subsequent X-ray diffraction analysis.